A set of Forge Models - Students Work Cal Polytechnic School San Luis Obispo, Cal - Frank Aston::::::photographer::: (1911)
A set of Forge Models -- Students Work ...' An exhibit of tools and hardware made by students in the Forge Shop. Published in the Catalogue 1910-11 Catalogue (May 1911).